(untitled) (Papeles, 2011)
Habitually Foucault’s thought has been considered to be developed through two different and opposed methods: genealogy and archeology. It is said the first of them replaces de the second one. On the contrary, this paper states that Foucault´s methodology can be interpreted as one single method that includes genealogy and archeology, being two fundamental overlapped axes that cannot be separated.